Experimental Design Technique on Removal of Hydrogen Sulfide using CaO-eggshells Dispersed onto Palm Kernel Shell Activated Carbon: Experiment, Optimization, Equilibrium and Kinetic Studies - Habeeb, Omar Abed; K., Ramesh; Ali, Gomaa A. M.; R. M., Yunus (Springer, 2017)
This study presents the use of chicken eggshells waste utilizing palm kernel shell based activated carbon (PKSAC) through the modification of their surface to enhance the adsorption capacity of H2S. Response surface methodology technique was used to optimize the process conditions and they were found to be: 500 mg/L for H2S initial concentration, 540 min for contact time and 1 g for adsorbent mass. The impacts of three arrangement factors (calcination temperature of impregnated activated carbon (IAC), the calcium solution concentration and contact time of calcination) on the H2S removal efficiency and impregnated AC yield were investigated. Both responses IAC yield (IACY, %) and removal efficiency (RE, %) were maximized to optimize the IAC preparation conditions. The optimum preparation conditions for IACY and RE were found as follows: calcination temperature of IAC of 880 °C, calcium solution concentration of 49.3% and calcination contact time of 57.6 min, which resulted in 35.8% of IACY and 98.2% RE. In addition, the equilibrium and kinetics of the process were investigated. The adsorbent was characterized using TGA, XRD, FTIR, SEM/EDX, and BET. The maximum monolayer adsorption capacity was found to be 543.47 mg/g. The results recommended that the composite of PKSAC and CaO could be a useful material for H2S containing wastewater treatment